Functional significance of coactivation of vagal and sympathetic cardiac nerves. - Koizumi, K (1982)
Simultaneous recording of activity in the vagal and sympathetic supplies to the heart has revealed that in reflexly and centrally evoked activity these two "antagonists" do not necessarily change action reciprocally. Coactivation occurs in chemoreceptor reflexes and related reactions, upon stretching of the sinoatrial nodal region of the right atrium and when certain hypothalamic regions are stimulated. The objective of the present work was to assay the physiological importance of coactivation of the two potentially antagonistic cardiac nerves in anesthetized dogs. Output from the heart was monitored by recording volume flow in the thoracic aorta just below the aortic arch; cardiac contractility was measured as left ventricular dp/dt. Tape recordings of vagus and sympathetic nerve activity during chemoreceptor and baroreceptor reflexes, during reciprocal and nonreciprocal changes produced by hypothalamic stimulation, and during hypoxia and hypercapnia were used to trigger stimulators feeding a stimulus per action potential to cardiac vagus and sympathetic nerves after central connections were cut. The vagus stimulation alone produced a decrease in aortic blood flow; stimulation of the sympathetic nerve alone resulted in increased aortic blood flow. Simultaneous stimulation of vagus and sympathetic, however, produced an even greater cardiac output (measured by aortic blood flow). Intermediate degrees of heart rate and strength of myocardial contraction were maintained in coactivation. Obviously, an association of increased vagus and sympathetic actions, which can be effected reflexly or by action of higher centers, is of physiological benefit. In control reactions that relate cardiac function to body need, both reciprocal and synergistic actions (coactivation) of cardiac nerves are used.